The legal identity of indigenous peoples in Russian law : the case of the Sakha Republic (Yakutia) - Tumusova Mach, Tuyaara (HAL CCSD, 2023)
The objective of this thesis is to analyze Russian law concerning indigenous peoples in order to demonstrate that the identity question of indigenous communities raises a number of controversies in jurisprudential practice. The concept of “indigenous small-numbered peoples” existing in Russian law is often subject to an essentialist interpretation. From the point of view of bio-social theories of ethnicities, which remain popular in Russian academic discourse, the identity of ethnic groups is considered as a static and homogeneous given, based on blood ties. The historical and sociological study of the identities of the ethnic communities of the Republic of Sakha (Yakutia), one of the subjects of the Russian Federation, makes it possible to reveal their constructed character. Using an analysis of Russian case law, we show that the essentialist approach is dominant in judicial practice and that it is inappropriate to the complex reality of Russia's indigenous communities. This approach manifests itself on the one hand in cases concerning the identification of indigenous communities and their members and on the other hand in cases relating to the interpretation of the specific rights of indigenous peoples, in particular relating to the concepts of "traditional way of life" and “traditional activities”. The importance of this study lies in the fact that it sheds light on the political and social issues of the rights of indigenous peoples through the prism of their identities. L’objectif de cette thèse est d’analyser le droit russe concernant les peuples autochtones afin de démontrer que la question identitaire des communautés autochtones soulève un certain nombre de controverses dans la pratique jurisprudentielle. Le concept des « peuples autochtones peu nombreux » existant en droit russe fait souvent l’objet d’une interprétation essentialiste. Du point de vue des théories bio-sociales des ethnies, qui restent populaires dans le discours académique russe, l'identité des groupes ethniques est considérée comme une ...